The market value of energy efficiency in buildings and the mode of tenure - Konstantin A. Kholodilin; Claus Michelsen (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Concerns about global warming and growing scarcity of fossile fuels require substantial changes in energy consumption patterns and energy systems, as targeted by many countries around the world. One key element to achieve such transformation is to increase energy efficiency of the housing stock. In this context, it is frequently argued that private investments are too low in the light of the potential energy cost savings. However, heterogenous incentives to invest in energy efficiency, particularly for owner-occupants and landlords, may serve as one explanation. This is particularly important for countries with a large rental sector, like Germany. Nevertheless, previous literature largely focuses on the pay offs owner-occupants receive, leaving out the rental market. This paper addresses this gap by comparing the capitalization of energy efficiency in selling prices (rents) for both types of residences. For this purpose data from the Berlin housing market are analyzed in hedonic regressions. The estimations reveal that energy efficiency is well capitalized in apartment prices and rents. The comparison of implicit prices and the net present value of energy cost savings/rents reveals that investors anticipate future energy and house price movements reasonably. However, in the rental segment, the value of future energy cost savings exceeds tenants' implicit willingness to pay by factor 2.98. This can either be interpreted as a result of market power of tenants, uncertainty in the rental relationship, or the landlord-tenant dilemma.
Keywords: R21; R31; Q40; 330; energy efficiency; house price capitalization; rental/owner-occupied housing; hedonic analysis